A new approach for the prediction of speed-adjusted pump efficiency curves - Coelho, Bernardete (2020)
Researchers and engineers commonly rely on modelling and simulation computer programs to improve the management, design and operational efficiencies in water supply systems. The reliability of some efficiency measures, however, is known to be highly dependent on the modelling accuracy of the selected modelling/simulation tool. Although a number of papers have been recently published related to the use of variable-speed pumps in water networks, there are no relevant studies on the analysis and improvement of the methods used to model the behaviour of these pumps. Consequently, the present work focuses on the methods used to model efficiency curves of variable-speed pumps. A new approach for the prediction of the speed-adjusted curves is proposed and preliminary results using two distinct pumps are presented and discussed. The proposed method is capable of satisfactorily predicting the behaviour of the pumps, demonstrating its potential to be effectively used in modelling tools.